Yona of the dawn. 33 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2021)
"Forbidden from contacting Hak and the Four Dragons, Yona sneaks out of her room at Hiryuu Palace! But when she comes face-to-face with Su-won, what words will she have for her father's murderer? Later, Yona uncovers some past mysteries about Su-won's parents!"--Back cover.